SEBUAH UJIAN PENEGAKAN HUKUM KEJAHATAN KESUSILAAN (Kasus Video Mesum) - Triwanto - (Wacana Hukum, 2010)
Abstrct  :  The purpose of law enforcement is often faced with the exam in its implementation, especially related regulations in it are still in debate   and proving to be deepening as well as actors who have a high resistance Key  words : Examination of law enforcement, Crime morality